Estágio Profissional: A aventura e crescimento de uma Professora Estagiária" - Ana Rita Rodrigues Falcão (2019)
After completing the four years of academic training, the professional internship takes place, which is part of the study plan of the 2nd year of the Master's Degree in Physical Education Teaching in the Basic and Secondary School of the Faculty of Sports of the University of Porto, where it allowed to transmit the academic knowledge hitherto acquired in the field of practice, that is, to experience the "shock with reality", which is based on a set of surprises in relation to the imagined about the profession (Batista et al., 2012). This report was conducted under the guidance of the Advisor Teacher, presenting the process of evolution of the trainee teacher, carried out throughout the school year, and her critical reflections of learning and lived experiences. The report is divided into 5 chapters. Since the first one is the "Introduction", which makes a brief framing of the Professional Internship, as well as its structuring. The second "Personal Background" refers to the life story, the experiences that influenced this career choice, and the student-trainee's initial expectations. The third "Institutional Framework" portrays the professional internship at the institutional, legal and functional level, and also offers an analysis of the context in which the student-student practice and the legitimation of Physical Education took place. The fourth chapter, "Realization of Professional Practice", comprises the reflection on the three areas of teacher performance. It should be noted that in area 3, there is the action research study, on understanding what is the difference between the MED in the Short Term Unit (Basketball) and the Long Term Unit (Handball) in relation to the students' activity and its context. of class. Finally, the fifth chapter, "Conclusions and Prospects for the Future", presents a final balance of the internship year, with all the learning and transformations achieved, as well as ambitions for the future. The internship has undoubtedly become an enriching and knowledge-sharing space between teacher-students and student-teachers. KEYWORDS: SPORT